Teams In VUCA - Ways of Dealing with Uncertainty - Jolanta BIEŃKOWSKA; Czesław SIKORSKI (Communications of International Proceedings, 2022)
According to the currently popular acronym VUCA, the modern world is variable, uncertain, complex and ambiguous. However, these features are not just a set of separate factors. Submitting their significance to theoretical considerations in order to search for a correlation allowed a model to include various forms of team activity categorised depending on the degree of accompanying uncertainty. In the next stage of the thought experiment, three levels of uncertainty in team management were distinguished. The result is the systematisation of knowledge considering contemporary conditions and forms of operation in business and to indicate general guidelines for dealing with uncertainty at its subsequent stages.
Keywords: VUCA; uncertainty; volatility; complexity; ambiguity.